2013
DOI: 10.1002/jgrd.50670
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous, common‐volume lidar observations and theoretical studies of correlations among Fe/Na layers and temperatures in the mesosphere and lower thermosphere at Boulder Table Mountain (40°N, 105°W), Colorado

Abstract: [1] Simultaneous and common-volume observations of Fe density, Na density, and temperatures in the mesosphere and lower thermosphere were made for 12 nights with an Fe Boltzmann lidar and a Na Doppler lidar at the Table Mountain Lidar Facility (40.13°N, 105.24°W) near Boulder, Colorado, in August and September 2010. We derive the correlations among temporal variations of Fe/Na densities and temperatures, eliminating the covariance bias via computing the cross correlations between Fe (Na) density and Na (Fe) te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…The effective lifetime of the atomic species in the metal layer is defined as the layer abundance divided by the total meteoric influx. The mean abundances are 10.65 × 10 9 cm −2 and 3.45 × 10 9 cm −2 , respectively, for Fe and Na at Table Mountain for August–September 2010 [ Huang et al ., ]. The ratio of the Fe to Na column abundance equals 3.1, which is consistent with the measured flux ratio and also implies that the particle velocities must be slow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective lifetime of the atomic species in the metal layer is defined as the layer abundance divided by the total meteoric influx. The mean abundances are 10.65 × 10 9 cm −2 and 3.45 × 10 9 cm −2 , respectively, for Fe and Na at Table Mountain for August–September 2010 [ Huang et al ., ]. The ratio of the Fe to Na column abundance equals 3.1, which is consistent with the measured flux ratio and also implies that the particle velocities must be slow.…”
Section: Discussionmentioning
confidence: 99%
“…In sections 3 and 4 of their paper, Huang et al . [] provide detailed descriptions of the lidar specifications and measurement capabilities, the observational scenarios, and the data processing for this unique data set. The vertical constituent flux is defined as the expected value of the product of the vertical wind and the constituent density.…”
Section: Observationsmentioning
confidence: 99%
“…This study was enabled by the coordinated observations with two Na Doppler lidars of the Consortium of Resonance and Rayleigh Lidars (CRRL) at Boulder, CO, and Logan, UT, in collaboration with an AMTM [ Pautet et al , ] located at Bear Lake Observatory (41.9°N, 111.4°W) nearby Logan, in the night of 27 November 2013, from ~1 to 13 UT. Under the CRRL umbrella, the Consortium Technology Center, hosted by the University of Colorado Boulder, operates a Student Training and Atmospheric Research (STAR) Na Doppler lidar from the Table Mountain Lidar Observatory (40.1°N, 105.2°W) north of Boulder [ Smith et al , ; Huang et al , ], while the Utah State University (USU) lidar group operates a Na Doppler lidar from the USU campus in Logan (41.7°N, 111.8°W) [ Yuan et al , ].…”
Section: Coordinated Observations With Crrl Lidars and Usu Amtm In Thmentioning
confidence: 99%
“…They concluded that the overall correlation between Na and Fe could be well explained by their responses to wave dynamics, while chemistry played important roles in determining the structure of the metal layers. Huang et al [] further reported the correlations between temperature and Fe/Na. By using theoretical models of wave‐induced dynamics, they showed that these correlations between Fe and Na layers and those between temperature and Fe/Na layers could be largely reproduced assuming that the density fluctuation is induced only by dynamical effects of waves while ignoring the chemical effects.…”
Section: Introductionmentioning
confidence: 99%
“…Chen and Yi [] showed for the first time that the Fe and Na fluctuations are positively correlated on both the bottomside and the topside of the layers, whereas they are typically negatively correlated near 90 km. These features have also been verified by the simultaneous Fe and Na observations at Arecibo Observatory (AO), Puerto Rico (18.35°N, 66.75°W) [ Yue et al ., ] and at Boulder, Colorado (40°N, 105°W) [ Huang et al ., ]. Yue et al [] found that negative correlation occurred around the peaks of nightly mean Fe and Na densities only if there existed a distinguishable height difference between the Fe and Na peaks.…”
Section: Introductionmentioning
confidence: 99%